Efecto in vitro de fungicidas y biochar sobre Sclerotium rolfsii - Santos Ponce, Luis Miguel (2021)
In Ecuador, one of the main agricultural activities of small producers is the cultivation of beans (Phaseolus vulgaris L.). White rot, a disease caused by the fungus Sclerotium rolfsii, causes considerable losses in plantations; a situation that encourages the irrational use of fungicides, which induces resistance of the phytopathogen. For this purpose, the effect of fungicides and biochar on S. rolfsii in vitro was evaluated. Sensitivity to commercial fungicides was determined: carboxim-thiram, pentachloronitrobenzene, diphenononazole, propiconazole, copper sulfate pentahydrate, benomyl, carbendazim (2000ppm); the two aforementioned bezimmidazoles together with methyl thiophanate and low-dose thiabendazole (1, 10, 100 and 1000ppm). As a biofungicidal alternative, the effect of biochar (rice, cocoa and carob) was defined at different concentrations (1,3,5 g 100ml-1); of which the combination with benomyl and difenoconazole was established. A completely randomized experimental design with factorial arrangement was used. The comparison of means used was Tukey (p> 0.5). The effect of the treatments on the inhibition percentage (24, 48, 72, 96, 120, 144, 168, 192, 216 hours), number of sclerotia, percentage of viability was evidenced. The best inhibition results (100%) were presented by the fungicides carboxim-thiram, difenoconazole, pentachloronitrobenzene, propiconazole and copper sulfate pentahydrate, unlike the fungicides chlorothalonil, benomyl, carbendazim, methyl thiophanate and thiabendazole that did not prevent mycelial growth. The biochar of carob, rice stimulate growth (100%), while that of cocoa only delays it; It is considered not a reliable alternative for the disease control.